Estudo de uma amostra de 40 escolares do ensino infantil em atendimento educacional especializado no município de Mauá, São Paulo - Trindade, Telma Cristina dos Santos (2017)
Introduction: National guidelines on inclusive education are well established in the official documents dealing with the subject in Brazil. This situation leads municipalities to develop local strategies to meet this demand. Objective: to evaluate the proposal of attendance educational specialized (AEE), in the city of Mauá, SP, among preschool children. Method: transversal descriptive documental study. The records of 40 students, chosen at random, among the 159 students enrolled in the multifunctional resource room (SRM) in the year 2015 were reviewed. For each student, the information was transposed from 11 documents that show the transit from the request of the registration by the teacher of the regular room until the SRM's departure. Results and Conclusion: the proposal of the attendance educational specialized (AEE) in preschool education in the municipality of Mauá in São Paulo is based on the guidelines of the Ministry of Education and the current legislation. The assisted population is based on the use of SRM. Specific results showed that: the schools of the municipal network that offer SRM are adequate for the number of students registered with some deficiency; there is significant underreporting in the prevalence of students with a disability. Underreporting can be well evidenced in Intellectual Disability and Autism Spectrum Disorder. The documentation of the students enrolled allows to know the condition of the disability but does not establish a link between the planning of the teaching and the particularities of the disabled student. The general routine of care must undergo some adjustments such as greater number of weekly hours in intervention; greater interaction between the teachers of the appeal room and the regular classroom as well as greater participation of the family and evaluation of intervention methods. In addition, teachers need to be empowered to use standardized procedures that better define students' cognitive and behavioral profile as well as the functionality and skills they possess. It is recommended that a computerized system Special Educat with friendly access ll´ be installed, hosted on the homepage of the Secretariat of Education of Mauá .